Discontinuation and nonpublication of clinical trials for the pharmacologic treatment of posttraumatic stress disorder among military veterans. Issue 2 (14th February 2023) - Weygandt, Jonas; Moody, Morgan; Sajjadi, Nicholas B.; Greiner, Benjamin; Ford, Alicia Ito; Mazur, Anna; Hartwell, Micah
Abstract: Failures by researchers and clinicians to overcome barriers in veteran health–related research may result in clinical trial (CT) discontinuation and nonpublication. Such outcomes are a waste of limited academic resources. To determine rates of discontinuation and nonpublication among CTs for posttraumatic stress disorder (PTSD) with pharmaceutical interventions specific to the veteran population, we performed a systematic search of registered trials in ClinicalTrials.gov for pharmaceutical interventions for the treatment of PTSD. Extracted study characteristics included sample size, study design, trial status, phase, and funding source. Studies were classified as completed or discontinued based on the status listed in ClinicalTrials.gov. Descriptive statistics of trials were reported, and associations of trial termination and nonpublication were assessed using logistic regression. The final sample included 54 CTs, 15 of which (27.8%) had not been published within the FDA's required timeframe, and 11 (20.4%) were discontinued. The total number of trial participants was 3, 463, with a median of 37 (interquartile range: 15–92). Of the 54 trials, 12 (22.2%) were nonrandomized, and 42 (77.8%) were randomized. There were 25 (46.3%) trials that were in either Phase 3 or Phase 4, and 39 (72.2%) were government‐funded. We found high rates of CT discontinuation and nonpublication among PTSD pharmaceutical intervention studies in veterans, as has been shown in other fields of research.